Community Based Approach: Empowering Persons with Disabilities - Hasan, Halid; Nikmah, Farika; Dwi Pribadi, Joni (International Journal Of Humanities Education and Social Sciences (IJHESS), 2024)
This study aims to analyze the implementation of empowerment of people with disabilities by Lingkar Sosial. Lingkar Sosial is a social organization that accommodates people with disabilities in Indonesia. In Indonesia, related to empowerment of disabilities is regulated by Government Regulation No. 52 of 2019 concerning Achieving Welfare for People with Disabilities. This study uses primary data obtained from interviews and secondary data from literature reviews as supporting materials. Furthermore, the data was analyzed using a qualitative approach. The results of the study indicate that Lingkar Sosial has an important role in empowering people with disabilities through economic, social and cultural empowerment. Lingkar Sosial has played a good role, there has been a structured and continuous work program every year, collaborating with various parties, and development for staff in managing people with disabilities. For sustainability, it is necessary to further improve cooperation with the government, academics and other parties that can strengthen the role of Lingkar Sosial.